Lipid Profiles in Systemic Lupus Erythematosus- An Update - Rahman, Shahana A; Islam, Md Mofizul; Islam, Md Imnul (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2015; VOL 39 (2) :88-92